2016
DOI: 10.1073/pnas.1522080113
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-responsive clustered nanoparticles for improved tumor penetration and therapeutic efficacy

Abstract: A principal goal of cancer nanomedicine is to deliver therapeutics effectively to cancer cells within solid tumors. However, there are a series of biological barriers that impede nanomedicine from reaching target cells. Here, we report a stimuli-responsive clustered nanoparticle to systematically overcome these multiple barriers by sequentially responding to the endogenous attributes of the tumor microenvironment. The smart polymeric clustered nanoparticle (iCluster) has an initial size of ∼100 nm, which is fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
408
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 647 publications
(412 citation statements)
references
References 49 publications
4
408
0
Order By: Relevance
“…These NPs undergo particle size change [34] , surface charge status switching [35] , or a hydrophobic to hydrophilic transition [36] by responding to the pH drop in the weakly acidic microenvironment of tumor or cancer cells. For instance, Wang et al recently reported a novel set of intelligent cluster (iCluster) NPs to improve the tumor penetration and distribution of the poly(amidoamine) (PAMAM) prodrug [37] . The NPs were composed of two distinct components.…”
Section: Overcoming Extracellular Barriers Using Nanomedicinementioning
confidence: 99%
See 1 more Smart Citation
“…These NPs undergo particle size change [34] , surface charge status switching [35] , or a hydrophobic to hydrophilic transition [36] by responding to the pH drop in the weakly acidic microenvironment of tumor or cancer cells. For instance, Wang et al recently reported a novel set of intelligent cluster (iCluster) NPs to improve the tumor penetration and distribution of the poly(amidoamine) (PAMAM) prodrug [37] . The NPs were composed of two distinct components.…”
Section: Overcoming Extracellular Barriers Using Nanomedicinementioning
confidence: 99%
“…The PAMAM prodrug penetrated deeply into the tumor, owing to the small particle size (~5 nm). Subsequently, the prodrug performed its antitumor function by being converted to cisplatin in the reducing environment of the cytosol ( Figure 1B) [37] . In a multilayer spheroidal cancer (MSC) model derived from BxPC-3 human pancreatic cancer cells, the hydrophobic PCL core (with red fluorescence labeling) of the iCluster NPs was observed to attach to the periphery of MCSs without a noticeable distribution in the internal area, after a 24 h incubation at a pH of 6.8.…”
Section: Overcoming Extracellular Barriers Using Nanomedicinementioning
confidence: 99%
“…In principle, this transition would make DNPs inclined to aggregate and thus slow down reentry into the blood stream because of its inherently hydrophobic nature, which consequently leads to a locally long‐term entrapment of drug‐vehicle system within neighboring tumor cells. And, the photothermal effect of PDA can trigger the release of small DNPs (≈5 nm) that enable deep and uniform penetration into more cancer cells, ultimately enhancing the chemotherapy of the DOX 34, 35. Attractively, the structure alteration will simultaneously induce a selectively fast drug release, favoring the enhanced drug efficacy inside tumor cells and finally realizing the chemo‐/photothermal synergistic therapy of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, positively charged oligoarginines have raised special interest, which possess several advantages including cell penetrating, nucleic acids binding capability, synthetic versatility, accessibility for tagging/labeling, and the easy design of various stimuli‐responsive sequences 29, 30, 31. At present, various stimuli‐responsive “smart” nanostructures have been developed according to the heterogeneity of extra‐ and intratumoral microenvironments, such as low pH, altered redox potential, hypoxia, and dysregulated enzymes, which allow spatially controlled release of the therapeutics only in the sites of interest to improve therapeutic efficiency 32, 33, 34, 35. For instance, the concentration of glutathione (GSH) is remarkably higher in tumor cells (10 × 10 −3 m ) compared to that in the blood plasma whose concentration is about 2 × 10 −6 to 10 × 10 −6 m 36.…”
Section: Introductionmentioning
confidence: 99%